STUDI TENTANG MINAT BELI E-TOLL CARD di KOTA SEMARANG - Agung Purnama, Cahaya; Widiyanto, Ibnu (Diponegoro Journal of Management, 2012)
E-toll card is a new innovative product of electronic money.This study was conducted to investigate the itention of toll users to buy e-toll card. how much consumers to buy the product e-toll card. This study aimed to analyze the effect of promoting attractiveness, perceived ease of use, perceived usefulness, and price on buying intention of e-toll card in the city of Semarang as the dependent variable. In this study, observer take 150 respondents that were taken by using a purposive sampling technique. Analysis using SPSS 16.0, including, reliability test, validity test, classic assumptions test, multiple regression analysis, hypothesis testing via the F and T test, and analysis of the coefficient of determination (RÂ²). Percieve Usefulness showed the greatest regression coefficient. Percieve Usefulness is the most important factor influencing the Buying Interest of consumers who buy e-toll card product. The second important factor is the Percieve of Ease of Use than Price and The Attractiveness Effect of Promotion as the third and Â factors that influence the Consumers Buying Interest. The coefficient of determination (adjusted R2) of 0,816 or 81,6 percent of the coefficient of determination means the model is good enough. The fourth independent variable in this study could explain 81,6 percent of the purchase decision variables. While the rest of 18.4 percent is explained by variables other than the four variables used in this study.